Risk factors of acute otitis media among infants in a tertiary care hospital in Rawalpindi: a descriptive cross-sectional study - Mumtaz Khan, Tayyab; Akram, Jehanzeb; Muneer, Fahad; Ilyas, Daniyal; Ahmed, Hafiz Muhammad; Khan, Asghar; Naeem, Muhammad Ahsan; Hafeez, Umair; Nawab, Fareena; Nasir, Muhammad Waleed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Acute otitis media (AOM) is the second most common disease of childhood. Many factors play role in the causation of AOM. However, the research-based data on risk factors for AOM in infants is still inadequate. Objective were this study aimed to determine the risk factors for AOM in infants with AOM. Methods: This descriptive cross-sectional study was conducted among 189 infant patients with AOM in the otorhinolaryngology outpatient department of allied hospital of Rawalpindi medical university, Rawalpindi. Established inclusion and exclusion criteria and non-probability convenience sampling technique were utilized for the selection of patients. After taking informed consent, data were collected through a self-adapted questionnaire. Descriptive analysis was accomplished through SPSS version 25. Results: AOM was more common among patients who had, an age group with a range of 9-12 months (41.28%), male gender (55.02%), lower birth order (49.73%), mothers with illiterate educational status (53.96%), mothers with the job (57.14%), lower socioeconomic status (59.25%), used bottle-feeding (46.56%), supine position during feeding (61.37%), used a pacifier (67.73%), poor feeding hygiene (58.21%), unvaccinated pneumococcal status (57.15%), and large family (63.50%). In the case of family ear infection and passive smoking, AOM incidence was more frequent among infants whose family had no history of ear infection (69.85%) and no smoking exposure (53.44%). Conclusions: In short, the age group with a range of 9-12 months, male gender, low birth order, illiterate mothers, mothers with the job, lower socioeconomic status, bottle-feeding, supine feeding position, pacifier use, poor feeding hygiene, unvaccinated pneumococcal status, and large family size, all raise the risk of AOM incidence in infants.